Genome-wide transcriptomic analysis identifies candidate genes involved in jasmonic acid-mediated salt tolerance of alfalfa - Yang, Tianhui; Tian, Mei; Gao, Ting; Wang, Chuan; Wang, Xiaochun; Chen, Caijin; Yang, Weidi (PeerJ, 2023)
Soil salinity imposes a major threat to plant growth and agricultural productivity. Despite being one of the most common fodder crops in saline locations, alfalfa is vulnerable to salt stress. Jasmonic acid (JA) is a phytohormone that influences plant response to abiotic stimuli such as salt stress. However, key genes and pathways by which JA-mediated salt tolerance of alfalfa are little known. A comprehensive transcriptome analysis was performed to elucidate the underlying molecular mechanisms of JA-mediated salt tolerance. The transcripts regulated by salt (S) compared to control (C) and JA+salt (JS) compared to C were investigated. Venn diagram and expression pattern of DEGs indicated that JS further altered a series of genes expression regulated by salt treatment, implying the roles of JA in priming salt tolerance. Enrichment analysis revealed that DEGs exclusively regulated by JS treatment belonged to primary or secondary metabolism, respiratory electron transport chain, and oxidative stress resistance. Alternatively, splicing (AS) was induced by salt alone or JA combined treatment, with skipped exon (SE) events predominately. DEGs undergo exon skipping involving some enriched items mentioned above and transcription factors. Finally, the gene expressions were validated using quantitative polymerase chain reaction (qPCR), which produced results that agreed with the sequencing results. Taken together, these findings suggest that JA modulates the expression of genes related to energy supply and antioxidant capacity at both the transcriptional and post-transcriptional levels, possibly through the involvement of transcription factors and AS events.
Keywords: Salt stress; Transcriptomic analysis; Alternative splicing; Alfalfa; Jasmonic acid